Perancangan Aplikasi Penyandian Agenda Pribadi Menggunakan Algoritma Kunci Public Elgamal - Yudistira, Dharma (Journal of Computing and Informatics Research, 2022)
In this final project, an encryption is created that is integrated with the existing agenda encoding application to add security to the security process on the mobile device. By using the ElGamal encryption method, it is hoped that the encryption process carried out through mobile devices will be more secure. Because, there is a public key and a private key that is only known by the user. The resulting output is ciphertext which when the user wants to read it, it is necessary to carry out the decryption process. In addition, in the encryption process for the same plaintext, different ciphertexts are obtained, but in the decryption process, the same plaintext is obtained. Thus, making the agenda safer than before.